(untitled) - Thibodeau, Gary A. (St. Louis ( Missouri ), 2005)
Offering a student-friendly writing style, this text presents a body systems approach with a strong emphasis on vocabulary and basic anatomy and physiology concepts, as well as the basic mechanisms of disease and pathologic conditions associated with each body system. This comprehensive text is dominated by two unifying themes: the complementarity of structure and function and homeostasis. The integrating principle of homeostasis is used to show how "normal" structure and function is achieved and maintained. Failures of homeostasis are shown as basic mechanisms of disease. The reader is drawn into the subject by superior illustrations, including cadaver dissections, and other student-friendly features.
Keywords: Human anatomy,Human physiology,Physiology, pathological